(3JMQjQ MGTjI CHj GdaJM Ydi TQM CTcGd GdJCSjSs - (3MjOQ Hf CMeO GdcQOi GdMSjfj CHGOis; (3bGVj RGOg ehSi LdHj , ehSi Hf eMeO Hf eMehO GdQhej, UdGM GdOjf,J (B840 (3g` s ((3eMeO GdTgjQ HGdWfWGhi s)
(3ChdgG (B:s
(3hHYO ajbhd MjOQ Hf CMeO GdcQOi GdMSjf CHGOi deG cGfJ fSNI MGTjI CHj GdaJM eMeO GdgGOi GdJi YfOfG Ydi TQM CTcGd GdeSei HJMaI GdQFjS ai TQM CTcGd GdJCSjS dehdGfG ehSi GdTgjQ HbGVi RGOg GdQhei s
(3BNQgG (B:s
(3JeJ MGTjg CTcGd GdJCSjS s
(3CTcGd GdJCSjS GfXQ cTa GdXfhf M(B1 (3U` (B105s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B328 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B47s
Keywords: (3GdQjGVjGJs